The human capital risk reporting of listed South African companies: Exploring a reporting framework to support corporate governance - Monique Bruwer; Salomé Elizabeth Scholtz; Leon T. de Beer; Johanna Christina Rothmann (Administrative Sciences, 2022)
Despite the importance and requirement of integrated reporting on human capital (HC), research indicates a lack of reporting frameworks and adequate disclosure in organization reports. Thus, a unique research opportunity is created for researchers to determine what is being presented in reports and how it correlates with human resource management. This article investigates HC reporting practices and proposes a risk reporting framework in support of corporate governance. A qualitative method utilizing qualitative document analysis was followed to analyze a purposive sample (n = 39) of Johannesburg Stock Exchange top 40 listed companies' annual integrated reports of 2020. Overall, companies followed a widely accepted risk management approach, with inconsistencies in the phases and methods of reporting the risk management phases directed at HC. The magnitude of the risk to the companies is also not understood. The most commonly reported HC risks were employee growth and development, diversity and inclusion, career paths, and employee turnover and turnover intention. Employee work-related well-being was largely neglected. An interesting finding is that the reported risks were metrics-deprived. Current HC practices are backward-looking instead of forward-looking, and they are fragmented. Therefore, an HC reporting framework is suggested for future research that addresses the gaps in integrated reports.
Keywords: 350; corporate governance; human capital; human capital risk management; human capital risk reporting; reporting framework